2002
DOI: 10.1093/ndt/17.4.587
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term renal injury in ANCA‐associated vasculitis: an analysis of 31 patients with follow‐up biopsies

Abstract: This is the first study to quantify glomerular changes between two time points in patients with renal vasculitis. Our results suggest that, on average, no new glomeruli are recruited into the active disease process. The sum of the percentage of crescentic and sclerotic glomeruli in the initial biopsies is larger than the percentage of sclerotic glomeruli in the follow-up biopsies. Thus, therapy seems not only to prevent normal glomeruli from being recruited into the active disease process for a certain time, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 17 publications
2
34
1
2
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13] One consistent finding in these studies is the relationship between a high percentage of normal glomeruli that are not affected by the disease process and favorable renal outcome. In fact, the percentage of normal glomeruli is a strong predictor, possibly the best his-tologic predictor, of short-or longterm renal outcome.…”
mentioning
confidence: 67%
“…[5][6][7][8][9][10][11][12][13] One consistent finding in these studies is the relationship between a high percentage of normal glomeruli that are not affected by the disease process and favorable renal outcome. In fact, the percentage of normal glomeruli is a strong predictor, possibly the best his-tologic predictor, of short-or longterm renal outcome.…”
mentioning
confidence: 67%
“…52,90,93 In contrast, more fibrotic changes are recorded in MPO-AAV, 93,94 reported as interstitial fibrosis in addition to fibrous crescents (19% in MPO-AAV versus 10% in PR3-AAV) 52 and obliterated glomeruli (25% in MPO-AAV versus 15% in PR3-AAV). 90 Since chronic features are known to be associated with bad renal outcome 52,95 patients with MPO-AAV may have worse renal survival than patients with PR3-AAV. Data on this matter remain, however, inconclusive.…”
Section: Histopathologic Featuresmentioning
confidence: 99%
“…None of the six patients had active vasculitis on renal biopsy, again suggesting that persistent hematuria could represent damage [4]. In a report of 31 patients undergoing repeat biopsy for suspected renal flare, 13% of biopsies did not have active glomerulonephritis [5]. Furthermore, a recent retrospective analysis of the impact of hematuria duration on one year estimated glomerular function rate (e-GFR) in AAV patients concluded that hematuria persistence for more than 90 days from the time of renal biopsy was not associated with lower one year e-GFR [6].…”
Section: Persistent Hematuria In Anca Vasculitismentioning
confidence: 88%